Improvement of Continuous Upright Writing Skills Through The Use of Fine Writing Media in Grade I Students of SDN Gelang 2 Tulangan Sidoarjo - Rahayu, Siti; Sukartiningsih, Wahyu; Subrata, Heru (International Journal of Emerging Research and Review, 2024)
Objective: This research was conducted in an effort to improve students' skills in continuous upright writing through the use of fine writing book media. The subjects of the study were students of SDN Gelang 2 Tulangan Sidoarjo class I odd semester of the 2023/2024 academic year with a total of 25 students. The purpose of his research is to improve the learning process with the hope of improving the quality of learning and having an impact on student learning outcomes Method: This study used two-cycle Classroom Action Research (PTK) using the model of Stephen Kemmis and Robin Mc Taggart, consists of four stages that must be passed including; (1) planning, (2) acting, (3) observing, and (4) reflecting in a related spiral. Results: The results of research on success in continuous upright writing skills through the use of fine writing book media in grade I students of SDN Gelang 2 Tulangan Sidoarjo showed an improvement. Indication of the achievement of the final evaluation results of research in the pre-research student scores ≥ 70 amounted to 8 people or 32%; in the first cycle the score of students ≥ 70 amounted to 18 people or 72%; and in the second cycle the scores of students ≥ 70 amounted to 24 people or 96%. Novelty: The implementation of continuous upright writing learning with the help of fine writing book media and learning using continuous upright letters at SDN Gelang 2 Tulangan Sidoarjo which has never been researched using the latest year's data.